Concentrations, homolog profiles, and risk assessment of short- and medium-chain chlorinated paraffins in soil around factories in a non-ferrous metal recycling park. (15th January 2022) - Weng, Jiyuan; Zhang, Peixuan; Gao, Lirong; Zhu, Shuai; Liu, Yang; Qiao, Lin; Zhao, Bin; Liu, Yin; Xu, Ming; Zheng, Minghui
Abstract: Chlorinated paraffins (CPs) are used as additives in metal processing in the metal smelting industry. Data on CPs in the environment near metal smelting plants are limited. The objectives of this study were to investigate the concentrations and congener profiles of CPs in soil around factories in a non-ferrous metal recycling park located in Hebei, China, and to investigate human exposure to CPs in the soil. The concentrations of short-chain CPs (SCCPs) and medium-chain CPs (MCCPs) were determined by two-dimensional gas chromatography with electron capture negative ionization mass spectrometry. The SCCP and MCCP concentrations in the soil samples were 121–5159 ng/g and 47–6079 ng/g, respectively. Generally, the CP concentrations in soils around the factories were relatively high compared with those near other contaminated sites and in rural and urban areas. There were significant correlations between the MCCP concentrations, some SCCP carbon homologs, and the total organic carbon content ( p < 0.05). The major SCCP and MCCP congener groups were C10 Cl6–7 and C15 –16 Cl5, respectively. Hierarchical cluster analysis and principal component analysis indicated that SCCPs and MCCPs in the soil might originate from extreme pressure additives containing CP-42 and CP-52 and CP-containing waste material from the factories. The concentrations in two samples collected near a metal recycling factory posed a moderate risk according to a risk assessment conducted using risk quotients. Further risk assessment showed that the CPs concentrations in soil did not pose significant health risks to either children or adults. Graphical abstract: Image 1 Highlights: SCCPs and MCCPs were determined in soil around metal processing facilities. Concentrations reached high level, the major groups were C10 Cl6–7 and C15 –16 Cl5 . CPs in soils could be sourcing from CPs-contain commercial products. There was no significant risk to human health under these circumstances.